Evaluation of insulin resistance in adolescent girl with menstrual irregularities - Kumari, Simi; Pankaj, Sangeeta; Sinha, Archana; Prasad, Dipali; Kumar, Ritesh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Polycystic ovary syndrome is most commonly recognized endocrinopathy in reproductive age group. The symptoms of PCOS vary with age, race, weight, and medications, which lead to the challenges of accurate diagnosis particularly in adolescent age group. Adolescent with PCOS most commonly encountered by gynecologist, for their menstrual irregularities. During early puberty, menstrual irregularities can occur normally due to immature Hypothalamo-pituitary-ovarian axis. Early detection of PCOS is required to control high risk of insulin resistance followed by reproductive and metabolic consequences latter on in life. Also diabetes mellitus is asymptomatic at early stage of insulin resistance and impaired glucose tolerance. Few studies have been conducted in Indian population, for prevalence of insulin resistance and metabolic syndrome in adolescents with PCOS, with varying results and hence further study is required. The aim and objectives of the study was to evaluate the presence of insulin resistance in adolescents with menstrual disorders persisting 2 years after menarche. Methods: A Cross sectional Study consisting of 102 adolescent girls done in Gynecology Outpatient Clinic of the Indira Gandhi Institute Of Medical Science Biochemical analysis was done on(day 3 to day 5) of menstruation for clinical/laboratory hyperandrogenism ,and various cause of anovulation. HOMA-IR value was evaluated for insulin resistance by following formula: fasting serum insulin (μU/ml) × fasting plasma glucose (m mol/l)/22.5. The 2003 Rotterdam consensus workshop criteria were used for ultrasonographic feature of polycystic ovarian syndrome. Results: Most common pattern of menstrual irregularities was Oligomenorrhea. 4 (7.84%) cases had insulin resistance (HOMA-IR >3.9) and 25 (49.01%) cases had elevated HOMA-IR values (HOMA-IR >1). PCOS was seen in 35.29% of cases and only 1.96% of control. Conclusions: Adolescents with persistent menstrual irregularities even after two year of menarche, especially with oligomenorrhea and hypomenorrhoea, more frequently have the diagnosis of PCOS and also present with elevated HOMA-IR values.